Global energy crunch: how different parts of the world would react to a peak oil scenario - Friedrichs, J (Elsevier, 2010)
Peak oil theory predicts that oil production will soon start a terminal decline. Most authors imply that no adequate alternate resource and technology will be available to replace oil as the backbone resource of industrial society. This article uses historical cases from countries that have gone through a similar experience as the best available analytical strategy to understand what will happen if the predictions of peak oil theorists are right. The author is not committed to a particular version of peak oil theory, but deems the issue important enough to explore how various parts of the world should be expected to react. From the historical record he is able to identify predatory militarism, totalitarian retrenchment, and socioeconomic adaptation as three possible trajectories.